Rola południowej Galii w produkcji i handlu winem w VI w. p.n.e. – II w. n.e. na tle przemian politycznych w zachodniej części Morza Śródziemnego - Góralczyk, Agnieszka (Folia Praehistorica Posnaniensia, 2021)
The article describes the role of southern Gaul in the production and trade of wine, with particular consideration for the Gauloise flat-bottomed amphorae produced in this area. It provides a brief outline of the history of this area of Mediterranean basin, shaped by the political and economic activities of several Mediterranean peoples – Phoenicians, Greeks, Carthaginians, Etruscans and Romans. It discusses the types of archaeological sites where the remains of amphorae for Gallic wine were discovered, exemplary stamps characteristic of southern Gaul and the influence of the Romans on the emergence and development of the culture of producing and consuming wine in southern Gaul